How Economic Systems React to Financial Regulation As a Stimuli: A Comprehensive Analysis Using Different Cases of Economies - Garg, Shubhra; Thakur, Mamta (Journal of Commerce and Trade, 2021)
IFRS are a set of guidelines issued by IASB, an independent organisation, it is an ideal reporting standard issued in order to regulate the accounting and the way various countries do that. In this paper we have tried to analyse the economic impact, both at the macro and micro level while we touch across different ideas related to the topic. We have chosen a comprehensive approach and have tried to show how this actually affects all the stakeholders. IFRS remains under intense scrutiny for its effectiveness in different settings. While it continues to have both short run and long run consequences. We have taken two cases of Europe and Latin America, and then we tried to understand the way the US GAAP and IFRS and are different from each other. Our primary aim was to reflect on how different stakeholders react to the changes made in the Financial Accounting Systems in their countries. We have also taken up the case of Italy where we have tried to highlight how the debt is substantiated using IFRS. We offer evidence of economically significant growth in institutional holdings in required IFRS adopters based on annual and quarterly firm-level studies and quarterly country-level tests. In comparison to a benchmark sample of non-adopters, institutional ownership and the number of investors grow after first-time IFRS reporting for mandated IFRS adopters. Classification-JEL: M4